OC-041 Changes in the expression of cellular iron transport machinery occur in pre-neoplastic lesions within the colon in both sporadic and familial polyposis. (23rd September 2015) - Brookes, M J; Ford, S; Caldwell, G; Jones, C; Iqbal, T; Tselepis, C
Abstract : Introduction: Sporadic colorectal adenocarcinoma (CRC) develops through the adenoma-carcinoma sequence involving in the tumour suppressor gene adenomatous polyposis coli (APC). Familial adenomatous polyposis coli (FAP) is a condition in which germline mutations in APC lead to early adenoma and tumour formation. Mutations in APC lead to increased Wnt signalling, the main oncogenic pathway in colon cancer, upregulating c-myc. Increased expression of the cellular iron import proteins (TfR1 and DMT-1) are found in CRC, and lead to increased intracellular iron. The aim of this study is to determine whether these changes can be found in pre-cancerous adenomatous polyps in sporadic and familial adenomatous polyposis. Methods: Colonic tissue from i) sporadic adenomas (n=15) and ii) familial adenomatous polyposis coli (n=10) was collected with matched normal colon. Real-time PCR was used to determine the expression of the iron transport proteins (TFR1, DMT1, ferroportin and ferritin) and c-myc. Results: Sporadic and familial adenomatous tissue showed a significant fold increase in TfR1, DMT1 and c-myc expression in 15/25, 16/25 and 14/25 tissue samples, respectively. Furthermore both TfR1 and DMT1 were tightly correlated with c-myc expression (R 2 >0.94 and 0.81, respectively). Conclusion: This study demonstrates that changes in the expression of iron transport machinery occur in the pre-cancerous adenomatous polyps in both sporadic and familial polyposis and may be regulated by the oncogene c-myc.